The Effect of Education by Leaflet and Audio-Visual Media on the Use of Insulin at Kimia Farma Pharmacy Hasanuddin Makassar - Nur Chaerunnisa (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2022)
Backgrounds: At Kimia Farma Hasanuddin Pharmacy Makassar, researchers found problems in the form of type 2 diabetes patients experiencing confusion and not even knowing how to inject insulin properly. This action results in insufficient use or overdose and injection timing that is not in accordance with the schedule set by the clinician, so this condition can cause hypoglycemia. This study aims to analyze the effect of education through leaflets and audio-visual media on the correct use of insulin at Kimia Farma Hasanuddin Pharmacy Makassar. Methods: The research approach used is quantitative research, using a quasi-experimental method with a one-group pretest-posttest design. The sample in this study amounted to 78 people, consisting of 39 people in the counseling group with leaflet media and 39 people in the audio-visual counseling group. Data analysis used univariate and bivariate analysis with paired sample t-test and independent sample t-test using SPSS 20.0 program. Results: Several results were obtained; There is an effect of leaflet and audiovisual media education on the correct use of insulin; There was a significant difference in knowledge (significantly) between the leaflet media group and the audiovisual group (p-value 0.018); There was no significant (significant) difference between the leaflet media group and the audiovisual group, and there is no significant (significant) difference in the mean of action between the leaflet media group and the audiovisual group. Conclusions: Leaflet Media Education has a higher influence than the Audio-Visual Media Education group as evidenced by the statistical test results.